Valorization of CTC tea waste through kombucha production and insight into GC-MS based metabolomics - Soumya Majumder; Arindam Ghosh; Sumedha Saha; Sukanya Acharyya; Sourav Chakraborty; Sahadeb Sarkar; Malay Bhattacharya (jurnal1, 2022)
This research paper is aimed to deliver a novel approach to prepare a popular probiotic beverage i.e., kombucha from infusion of tea waste to valorize the by-product of tea industry. In this study, a GC-MS based approach in combination with preliminary in vitro biochemical analysis was used to investigate the metabolic profiles, especially the antioxidant compounds produced during the fermentation of waste tea infusion. Waste tea infusion was found to be rich in xanthosine, the precursor of caffeine while the fermented sample was seen to be rich in more bioactive secondary metabolites derived from the substrate compounds i.e., xanthosine and sucrose. In addition, GC-MS based metabolomics helped to propose biosynthesis pathways of the metabolome which suggest the later breakdown of xanthosine and other substrate components into microbial metabolites during fermentation process. These findings are expected to be useful for further studies on production of bioactive formulations from tea waste.